2020
DOI: 10.1590/1980-5373-mr-2020-0013
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of the Sawn Surface of Monocrystalline Silicon Cut by Endless Diamond Wire Sawing

Abstract: The aim of this study was to investigate the influence of the cutting parameters on monocrystalline silicon cut by diamond wire sawing. The sawn surface was analyzed in terms of surface morphology, surface roughness, material removal mechanism and residual stress (by Raman spectroscopy). The surface morphology exhibited evidence of both material removal mechanisms: the brittle mode and the ductile mode. The surface roughness increased with a high v f , which promoted the formation of craters on the sawn surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…As seen in the Raman spectra, the microgrooves region presented a bandwidth associated with the a-Si phase, indicating a more intense compressive state on the sawn surface. This higher compressive stress can be attributed to the surface formation by ductile cutting mode, which leads to the formation of smooth grooves on the sawn silicon surface [7]. Based on this nding, it can be stated that the stress state of the sawn polycrystalline silicon surface results from material removal in ductile regime.…”
Section: Brittle-ductile Transition and Residual Stress Due To Phase ...mentioning
confidence: 89%
See 1 more Smart Citation
“…As seen in the Raman spectra, the microgrooves region presented a bandwidth associated with the a-Si phase, indicating a more intense compressive state on the sawn surface. This higher compressive stress can be attributed to the surface formation by ductile cutting mode, which leads to the formation of smooth grooves on the sawn silicon surface [7]. Based on this nding, it can be stated that the stress state of the sawn polycrystalline silicon surface results from material removal in ductile regime.…”
Section: Brittle-ductile Transition and Residual Stress Due To Phase ...mentioning
confidence: 89%
“…This approach is associated with a higher material removal rate, lower cost per wafer and better surface quality, besides being environmentally friendly [5,6]. However, crystalline silicon has the typical characteristics of a brittle material and thus damage to surface integrity of the wafer, such as surface roughness, fractures, scratches, micro-cracks, residual stress and so on, is one of the most serious issues arising during the processing [7]. The silicon wafers must comply with stringent requirements of surface integrity to ensure the performance and lifetime of a solar cell.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that fast-growing wafer crystal had a large maximum residual shear stress. Erick et al [15] studied the influence of different slicing parameters on monocrystalline silicon wafers, and measured the residual stress of the silicon wafers after cutting by Raman spectroscopy. The results showed that the residual stress on the surface of the monocrystalline silicon wafer by wire saw slicing is compressive stress, and the residual compressive stress increases with the increase of the axial speed of the wire saw.…”
Section: Introductionmentioning
confidence: 99%